2013
DOI: 10.1111/1574-6941.12215
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization shape bacterial community composition in urban park soils? A case study in 16 representative Chinese cities based on the pyrosequencing method

Abstract: Although the geographical distribution patterns of microbes have been studied for years, few studies have focused on urban soils. Urbanization may have detrimental effects on the soil ecosystem through pollution discharge and changes in urban climate. It is unclear whether urbanization-related factors have any effect on soil bacterial communities. Therefore we investigated geographical patterns of soil microbial communities in parks in 16 representative Chinese cities. The microbial communities in these 95 soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
59
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 38 publications
14
59
2
1
Order By: Relevance
“…These results were similar to the findings reported by Xu et al . in soil from urban park soil in China44. They were also consistent with a study performed in New York City’s Central Park4550.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results were similar to the findings reported by Xu et al . in soil from urban park soil in China44. They were also consistent with a study performed in New York City’s Central Park4550.…”
Section: Discussionsupporting
confidence: 89%
“…Xu et al . suggested that urbanization factors have no significant correlation with α-diversity in urban parks44. However, in the current work, results showed that soil bacterial diversity had significant differences across urban ring road areas.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Besides the impact of RWI on soil resistome and the bacterial community, we also examined whether soil ARGs was shaped by soil properties, which were generally considered as important factors affecting soil microbes (Cytryn, 2013;Xu et al, 2014). In this study, soil pH (ranging from 3.76 to 7.57, Table S2) exhibited a significant and positive correlation with the enrichment of total ARGs, which was in consistence with the results of Tang et al (2015), which found the significantly positive correlations between soil pH (ranging from 5.63 to 7.55) and the relative abundances of several genes conferring resistance to tetracyclines and sulfonamides.…”
Section: Impacts Of Rwi On the Bacterial Communities In Urban Park Soilsmentioning
confidence: 99%